2019
DOI: 10.1162/ling_a_00315
|View full text |Cite
|
Sign up to set email alerts
|

Topic Strategies and the Internal Structure of Nominal Arguments in Greek and Italian

Abstract: The paper investigates investigates how Italian and Greek employ Clitic Left Dislocation (clld) to encode discourse topics. Greek is sensitive to the definiteness/referentiality of the topic, employing clld exclusively for referential topics and resorting to Topicalisation for non-referential/property denoting topics. By contrast, clld is the main topic-strategy in Italian including non-referential/property denoting topics. This contrast is shown to mirror variation in more general patterns of anaphoric relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…However, Alexopoulou & Folli (2019) abandon this account since, as they argue, it cannot explain why CLLD-ed indefinites in Italian can be in the scope of a universal. In Alexopoulou & Folli (2019), they develop an account according to which the clitic in Greek is obligatorily referential, therefore forcing a referential interpretation for the CLLD-ed indefinite. From the same reasoning, it follows that true quantifying expressions cannot be CLLD-ed.…”
Section: The Marked Cases: Clld and Focus (Svo And Ovs)mentioning
confidence: 99%
“…However, Alexopoulou & Folli (2019) abandon this account since, as they argue, it cannot explain why CLLD-ed indefinites in Italian can be in the scope of a universal. In Alexopoulou & Folli (2019), they develop an account according to which the clitic in Greek is obligatorily referential, therefore forcing a referential interpretation for the CLLD-ed indefinite. From the same reasoning, it follows that true quantifying expressions cannot be CLLD-ed.…”
Section: The Marked Cases: Clld and Focus (Svo And Ovs)mentioning
confidence: 99%
“…However, such differences are not directly related to our main concern and so we leave the issue to future further exploration. 46 Alexopoulou & Folli (2019) have suggested that a difference between Western Romance and Greek is that, while the former allows a null D, the latter does not.…”
Section: Journal Of Greek Linguistics 19 (2019) 3-57mentioning
confidence: 99%
“…This paper is concerned with the properties and the distribution of the indefinite determiner kati "some" in Greek. While kati is mentioned in some work on Greek indefinite NPs, see e.g., Haspelmath (2001); Lazaridou-Chatzigoga (2009); Giannakidou (2012); Alexopoulou and Folli (2019); and Etxeberria and Giannakidou (2021), among others, systematic studies of this determiner are scarce, with Tsoulas (2021) being a notable exception. The behavior of kati is intriguing, as it combines uniquely with plural nouns, although diachronically, as Holton et al (2019) report, other combinations were also possible.…”
Section: Introductionmentioning
confidence: 99%